Ko vsak uporablja svoj lastni jezik in razume svojega sogovorca - Pirih Svetina, Nataša (Vestnik za tuje jezike, 2016)
Intercomprehension is a communication practice where two persons speak their mother tongue and are able to understand each other without being taught the language of their adressee. It is a usual practice between languages that belong to the same linguistic family, for example Slavic, Romance or Germanic languages. In the article, the authors present the notion of intercomprehension as an alternative to communication in English as a lingua franca. That kind of communication was known among Scandinavians, whereas the first teaching method was developped for Romance languages (EuRomCom) at the beginning of the 21st century. Today, more methods exist including German and Slavic languages. In the article, the authors are enumerating some of them and also give a short outline of existing practices.
Keywords: medjezikovno razumevanje; jezikovne družine; romanski jeziki; Slavic languages; slovanski jeziki